Combined theoretical and experimental insights on DNA and BSA binding interactions of Cu(ii) and Ni(ii) complexes along with the DPPH method of antioxidant assay and cytotoxicity studies - Acharya P.; Kuila A.; Pramanik U.; Hathwar V.R.; Brandao P.; Mukherjee S.; Maity S.; Maity T.; Maity R.; Chandra Samanta B. (My University, 2025)
This present study delineates the syntheses, detailed characterization and anti-proliferative potential against SiHa (cervical cancer cell) of two mononuclear complexes of Cu(ii) and Ni(ii) using a Schiff base ligand (L) derived from 2-hydroxybenzaldehyde and N-methyl-propane 1,3-diamine. The crystallographic results show the centro-symmetric space group of orthorhombic nature (Pccn) for Cu(ii) complex (1) where the central Cu(ii) has an inversion center symmetry with six co-ordinations resulting in a distorted octahedral geometry. Whereas, in complex (2), the two independent Ni(ii) atoms present in the special position within version symmetry and form a distorted geometry of octahedral nature with six coordinations. Absorption spectral titrations with Calf Thymus (CT) DNA and the extent of the decrease in relative emission intensities of DNA-bound ethidium bromide (EB) upon adding the complexes reveal the parallel trend in DNA binding affinities for both the complexes but with a small extent of binding capabilities. Bovine serum albumin (BSA) interaction studies demonstrate that complex 1 exhibits more promiscuous binding with BSA as compared to complex 2 from the spectroscopic and theoretical approaches. α,α-Diphenyl-β-picrylhydrazyl (DPPH) free radical scavenging method shows a little antioxidant or free radical scavenging activity for both the studied complexes. Cytotoxicity studies against SiHa expressed that the percentage of cell viability was reduced with time whereas in the same concentration and conditions, the viability percentage was higher for 3T3-L1 (several normal cell lines of mouse). The fluorescence imaging obtained from acridine orange (AO) and ethidium bromide (EtBr) demonstrates that the colour of the cancer cells has changed gradually dictating the cell apoptosis from day 1 to day 3. © 2023 The Royal Society of Chemistry.